Poverty in the West Bank and Gaza - World Bank (Washington, DC, 2013)
This report's overarching objective is to increase understanding of the causes of poverty in order to find ways to reduce it among Palestinaians. Three broad messages emerge from this report: 1) Unless the Palestinian territories are able to achieve high levels of economic growth, the prospects for future poverty reduction are not encouraging. not only will the number of poor Palestinians grow rapidly, but their share in the population will also increase, which could become a socially destabilizing factor. 2) Unless Palestinians gain greater access to external markets and to better paying jobs, whether in Israel or in higher productivity occupations, it will be difficult for them to escape poverty. Presently, the majority of poor Palestinians live in households headed by working adults in low-paying jobs that do not provide sufficient income to raise their families to a minimally acceptable standard of living. 3) The formal safety net does not have the financial resources necessary to have a significant impact on poverty. Nevertheless, it can play an important role in helping to reduce destitution among households headed by the unemployable poor and even the temporarily unemployed. The report's four chapters compare poverty levels and discuss the microdeterminants of poverty; analyze the impacts of economic growth, income redistribution, and labor markets; detail the poverty map; and discuss improving the social safety net.